Pengaruh Media Busy Book Terhadap Kemampuan Literasi dan Motorik Halus Anak di TK Santa Clara Mamuju - Markus, Grace Octaviana; Saodi, Syamsuardi; Amriani, Sri Rika (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2025)
This study aims to determine how the use of busy book media can influence children's literacy and fine motor skills. The research adopted a quantitative approach with a quasi-experimental design. The variables in this study are busy book media (X) as the independent variable, and literacy and fine motor skills (Y) as the dependent variables, using a non-equivalent group design or quasi-experimental design. The population in this study consisted of 80 children. The sampling technique used was purposive sampling, with a total of 40 children as the sample—20 children in the experimental group and 20 children in the control group. The data collection techniques employed in this study included observation, testing, and documentation. The data were analyzed using descriptive statistical analysis and parametric statistical analysis through the paired sample t-test. The results showed a significant difference between the  group that used busy book media and the group that did not. Therefore, it can be concluded that the application of busy book media significantly enhances children's literacy and fine motor skills.